PENERAPAN MODEL UTAUT DALAM SISTEM PEMBELAJARAN E-LEARNING - Erma Delima Sikumbang (LPPM Universitas Bina Sarana Informatika, 2014)
E-learning is one of the technologies used for online learning students. With the e-learning process of students learning is no longer limited by space and time as it can be accessed anywhere and anytime quickly and easily. This study describes the results of research on the factors affecting the e-learning system with approaches Unified theory of acceptance and use of technology (UTAUT). Variables used in this study consists of exogenous and endogenous variables. Exogenous variables, namely, performance expectancy, effort expectancy, social influence and facilitating conditions and behavioral intentions are endogenous variables and user behavior. These results indicate that performance expectancy has a positive and significant correlatio (p=0.570) to behavioral intention as well as facilitating condition has a positive and significant correlation (p=0.612) to use behavioral.